E-084 Day-of-week effect on safety of elective brain aneurysm treatment. (23rd July 2022) - Lauzier, D; Cler, S; Jayaraman, K; Chatterjee, A; Osbun, J; Moran, C; Kansagra, A
Abstract : Introduction: Elective treatment of intracranial aneurysms comprises a large share of neurointerventional practice. With increasing demand for endovascular aneurysm treatment, there is a need to assess factors such as operator fatigue and time-related effects that may influence the development of clinical complications, particularly in the elective setting. Here, we review a large cohort of elective treatments to quantify the influence of weekday on post-treatment neuroimaging and occurrence of clinical complications. Methods: Clinical and imaging data for elective aneurysms treated endovascularly were retrospectively obtained from a high-volume center and analyzed. Emergent treatments for hemorrhagic or other aneurysms were excluded from analysis. Treatment procedures were classified based on the day of the week they were performed. For each procedure, any post-treatment cerebral angiography, axial neuroimaging, and clinical complications occurring prior to discharge were recorded as a proxy metric for known or suspected complications. To characterize the association between day-of-week and need for imaging or occurrence of complications, univariate analysis using the Chi Square test was performed. Results: In total, 1329 elective aneurysm treatments were included in this study. Cerebral angiography was performed after 2.3% (30/1329) of cases, axial neuroimaging was performed after 11.9% (158/1329) of cases, and complications occurred following 5.9% (78/1329) of cases. No trends in need for cerebral angiography were detected in univariate analysis. Need for axial imaging and occurrence of complications were more likely for cases performed on Wednesdays, with 17.4% (49/282) (p = 0.01) of cases needing axial neuroimaging and 9.6% (27/282) (p = 0.024) of cases resulting in clinical complications prior to patient discharge. Conclusions: Our exploratory analysis demonstrated a higher rate of post-treatment axial neuroimaging and clinical complications for patients electively treated on Wednesdays. While the precise reasons for this trend are unclear, it warrants further investigation to identify practice patterns that may unnecessarily contribute to complications or added cost. Disclosures: D. Lauzier: None. S. Cler: None. K. Jayaraman: None. A. Chatterjee: None. J. Osbun: 2; C; Medtronic, Microvention. C. Moran: 2; C; Medtronic, Cerenovus, Microvention, Stryker, Balt. A. Kansagra: 2; C; Microvention, Penumbra.